POSSIBLE WORLDS FOR FICTION. A RECONSTRUCTIVE APPROACH, WITH A PRACTICAL OUTLOOK INTO IAN MCEWAN’S ATONEMENT, ON CHESIL BEACH AND THE CHILD IN TIME - URIAN, Adriana Diana (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Possible Worlds for Fiction. A Reconstructive Approach, With a Practical Outlook into Ian McEwan’s Atonement, On Chesil Beach and The Child in Time. The present paper aims at presenting how the possible world framework can function for fictional worlds. It starts from presenting different perspectives on how fictional universes can be understood. It then grounds its reconstructive approach in modal logic theories, such as the ones postulated by Kripke and Lewis, attempting to find a possible world system which can be adapted and become custom-fit for fiction. The theoretical approach favorizes re-creations of the modal system for fiction, as presented by Marie-Laure Ryan or Ruth Ronen. The study of this particular topic is eclectic, putting together various perspectives on literature, fiction and modality. The theoretical input is accompanied by practical reverberations from the three novels presented in the title, which function as its scientific playground. REZUMAT. Lumile posibile și domeniul ficțional. O abordare reconstructivă cu aplicații practice în romanele lui Ian McEwan Ispășire, Pe plaja Chesil și Copilul furat. Prezenta lucrare își propune să prezinte modul în care sistemul lumilor posibile poate fi aplicat și lumilor ficționale. Demersul de cercetare pornește de la prezentarea unor perspective diverse asupra modului în care lumile ficționale pot fi înțelese. Apoi fixează abordarea reconstructivă în teoriile logicii modale, așa cum apar ele prezentate de Kripke sau Lewis, încercând să găsească un cadru modal care să poată fi adaptat și să fie relevant pentru studiul ficțiunii. Abordarea propusă favorizează re-creații ale sistemului modal pentru domeniul ficțional, cum ar fi teoriile lui Marie-Laure Ryan sau ale lui Ruth Ronen. Viziunea teoretică este una eclectică, analizând diverse perspective asupra literaturii, ficțiunii și modalității. Perspectivele teoretice sunt însoțite de exemplificări practice din cele trei romane expuse în titlu, acestea funcționând ca un ideal teritoriu practic. Cuvinte-cheie: lumi posibile, semantica lumilor posibile, ficțiune, lumi ficționale, ficțiune postmodernă, entități ficționale, logică modală Article history: Received 11 June 2024; Revised 25 October 2024; Accepted 15 September 2024; Available online 10 December 2024; Available print 30 December 2024.